Kecenderungan Terhadap Seni Rupa Modern Indonesia Di Lingkungan Korporat: Studi Kasus Di pt. Rahman Ramadhan Diandara - sagara mata dewa sagara mata dewa; Agus Cahyana; Farid Kurniawan Noo Zaman (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Abstract: This study aims to examine the tendencies of artistic taste among individuals in a professional corporate environment toward modern Indonesian visual art. Utilizing a qualitative art criticism approach, the study engages three paintings from the Perintisan, Mooi Indie , and Persagi periods as visual prompts. The results reveal that respondents’ visual preferences are shaped by educational background, visual experience, and a generally neutral office environment. Despite limited participation, the findings indicate that artworks with historical or emotional narratives receive more attention than purely decorative landscapes. This study contributes to understanding non-art audiences within professional settings